Pengetahuan Pasien Prolanis terhadap Manajemen Farmakoterapi Diabetes Melitus dan Hipertensi di Fasilitas Kesehatan Tingkat Pertama - Faradila Puspita Andarwati; Natacya Essensi Christivani; Natasha Triska Suri; Ni Kadek Yulia Pradnyani; Nira Dwi Anggraeni; Reni Kartika Dewi; Desy Nawangsari (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Diabetes mellitus (DM) and hypertension are non-communicable diseases with an increasing prevalence in Indonesia. According to the 2023 Indonesian Health Survey (SKI), the prevalence of diabetes mellitus among individuals aged 15 years and older reached approximately 11.7%, while hypertension affected around 30.8% of the population. These figures highlight the importance of sustainable chronic disease management, in which treatment success largely depends on patients' knowledge and ability to adhere to their medication regimens independently. This community service program aimed to assess the level of knowledge among participants of the Chronic Disease Management Program (PROLANIS) at Adipala 2 Primary Health Center and to provide education on the pharmacotherapy management of diabetes mellitus and hypertension. A quantitative descriptive method with consecutive sampling was employed involving 50 respondents. Data were collected using a structured questionnaire consisting of eight indicators related to medication adherence and proper drug administration. The results revealed excellent knowledge regarding daily medication adherence (100%) and avoiding double doses after missed medication (98%). However, limited understanding was found concerning the appropriate timing of glimepiride administration (50%) and the correct insulin injection procedure (38%). These findings indicate the need for more comprehensive pharmacotherapy education to improve medication safety, prevent medication errors, and optimize therapeutic outcomes among patients with diabetes mellitus and hypertension